Blood-feeding adaptations and virome assessment of the poultry red mite Dermanyssus gallinae guided by RNA-seq - Ribeiro, José M; Hartmann, David; Bartošová-Sojková, Pavla; Debat, Humberto; Moos, Martin; Šimek, Petr; Fara, Jiří; Palus, Martin; Kučera, Matěj; Hajdušek, Ondřej; Sojka, Daniel; Kopáček, Petr; et al. (Communications biology, 2023)
Dermanyssus gallinae is a blood-feeding mite that parasitises wild birds and farmed poultry. Its remarkably swift processing of blood, together with the capacity to blood-feed during most developmental stages, makes this mite a highly debilitating pest. To identify specific adaptations to digestion of a haemoglobin-rich diet, we constructed and compared transcriptomes from starved and blood-fed stages of the parasite and identified midgut-enriched transcripts. We noted that midgut transcripts encoding cysteine proteases were upregulated with a blood meal. Mapping the full proteolytic apparatus, we noted a reduction in the suite of cysteine proteases, missing homologues for Cathepsin B and C. We have further identified and phylogenetically analysed three distinct transcripts encoding vitellogenins that facilitate the reproductive capacity of the mites. We also fully mapped transcripts for haem biosynthesis and the ferritin-based system of iron storage and inter-tissue trafficking. Additionally, we identified transcripts encoding proteins implicated in immune signalling (Toll and IMD pathways) and activity (defensins and thioester-containing proteins), RNAi, and ion channelling (with targets for commercial acaricides such as Fluralaner, Fipronil, and Ivermectin). Viral sequences were filtered from the Illumina reads and we described, in part, the RNA-virome of D. gallinae with identification of a novel virus, Red mite quaranjavirus 1.
Keywords: kur domácí; Poultry Diseases; nemoci drůbeže; Virome; infestace roztoči; drůbež; Poultry; Animals; Mites; virom; RNA-Seq; sekvenování transkriptomu; zvířata; roztoči; Chickens; Mite Infestations